Mn-Co spinel coatings on Crofer 22 APU by electrophoretic deposition: Up scaling, performance in SOFC stack at 850 °C and compositional modifications. Issue 8 (July 2021) - Sabato, A.G.; Zanchi, E.; Molin, S.; Cempura, G.; Javed, H.; Herbrig, K.; Walter, C.; Boccaccini, A.R.; Smeacetto, F.
Abstract: Ceramic coatings for metallic interconnects play a key role in limiting corrosion and chromium evaporation in solid oxide cells. This study presents the upscaling of the electrophoretic deposition (EPD) technique to process Mn-Co spinels on real-dimension Crofer 22 APU interconnects and the test in a SOFC stack. Area specific resistance of long-term test conducted for 5000 h at 850 °C demonstrated that two-steps sintering has a significant influence on the coating performance; an area specific resistance degradation rate of 0.5 mΩ cm 2 kh −1 is recorded. Stack test, operated in fuel cell mode at 850 °C for 3000 h under application of 227 mA/cm², including 5 thermal cycles, demonstrated the effectiveness of the electrophoretically deposited Mn-Co spinel in limiting the oxide scale growth on the Crofer 22 APU. An advanced post mortem investigation showed the effectiveness of the EPD ceramic coating, even when considering different and complex surfaces of the Crofer 22 APU.